Anatomical and psychometric relationships of behavioral neglect in daily living. (April 2015) - Rousseaux, Marc; Allart, Etienne; Bernati, Thérèse; Saj, Arnaud
Abstract: Spatial neglect has been related to both cortical (predominantly at the temporal–parietal junction) and subcortical (predominantly of the superior longitudinal fasciculus) lesions. The objectives of this observational study were to specify the anatomical relationships of behavioral neglect in activities of daily living (N-ADLs), and the anatomical and psychometric relationships of N-ADLs on one hand and components of neglect (peripersonal neglect and personal neglect) and anosognosia on the other. Forty five patients were analyzed for behavioral difficulties in daily living (on the Catherine Bergego scale) and the main components of neglect (using conventional clinical assessments) during the first months post right hemisphere stroke. Voxel-based lesion-symptom mapping was used to identify brain areas within which lesions explained the severity of bias in each assessment (non-parametric permutation test; p <0.01, one tailed). N-ADLs was associated with lesions centered on the posterior part of the superior temporal gyrus and extending to the temporo-parietal junction, temporo-occipital junction and subcortical white matter (including the superior longitudinal fasciculus). Peripersonal neglect resulted from extended cortical lesions centered on the superior temporal gyrus and the inferior parietal gyrus, with subcortical extension. Personal neglect resulted predominantly from lesions centered on the somatosensory cortex and at a lesser degree on the superior temporal sulcus. Anosognosia resulted from lesions of the posterior inferior temporal gyrus and superior temporal gyrus. In anatomic terms, N-ADLs was strongly related to peripersonal neglect, and those relationships were also shown by the psychometric analysis. In conclusions, superior temporal gyrus and superior longitudinal fasciculus lesions have a pivotal role in N-ADLs. N-ADLs is principally related (anatomically and psychometrically) to peripersonal neglect, and at a lesser degree to anosognosia and personal neglect. Highlights: We explored the anatomy of neglect behavior in daily living in stroke patients We explored relationships of neglect behavior with neglect components and anosognosia Neglect behavior resulted from lesions centered on the superior temporal gyrus Neglect behavior and peripersonal neglect showed anatomic and psychometric associations Neglect behavior and anosognosia showed more limited relationships